The Genetics of Dementia - Farlow, Janice L.; Foroud, Tatiana (Seminars in Neurology, 2013)
Over the past decade, there has been a dramatic evolution of genetic methodologies that can be used to identify genes contributing to disease. Initially, the focus was primarily on classical linkage analysis; more recently, genomewide association studies, and high-throughput whole genome and whole exome sequencing have provided efficient approaches to detect common and rare variation contributing to disease risk. Application of these methodologies to dementias has led to the nomination of dozens of causative and susceptibility genes, solidifying the recognition that genetic factors are important contributors to the disease processes. In this review, the authors focus on current knowledge of the genetics of Alzheimer's disease and frontotemporal lobar degeneration. A working understanding of the genes relevant to common dementias will become increasingly critical, as options for genetic testing and eventually gene-specific therapeutics are developed.
Keywords: genetic risk factors; dementia; Alzheimer's disease; frontotemporal lobar degeneration